Molecular classification of tumour cells in a patient with intravascular large B‐cell lymphoma. (29th December 2017) - Bauer, W.M.; Aichelburg, M.C.; Griss, J.; Skrabs, C.; Simonitsch‐Klupp, I.; Schiefer, A.I.; Kittler, H.; Jäger, U.; Zeyda, M.; Knobler, R.; Stingl, G.
Summary: Background: Intravascular large B‐cell lymphoma (IVLBCL) is a rare type of extranodal LBCL. It is characterized by the proliferation of tumour cells exclusively intraluminally in small blood vessels of different organs. The clinical manifestation depends on the type of organ affected; additionally, a haemophagocytic syndrome can be observed in some patients. Objectives: The aim was to further understand the nosology of this lymphoma as, due to its rarity and in spite of detailed immunohistochemical investigations, its exact nosology is only incompletely understood. Methods: We used microarray‐based analysis of gene expression of tumour cells isolated from a patient with primary manifestation of the lymphoma in the skin and compared it with various other diffuse LBCLs (DLBCLs) as well as a previously published DLBCL classifier. Results: In unsupervised analyses, the tumour cells clustered together with non‐germinal centre B‐cell (non‐GCB) DLBCL samples but were clearly distinct from GCB‐DLBCL. Analogous to non‐GCB DLBCL, molecular cell‐of‐origin classification revealed similarity to bone‐marrow derived plasma cells. Conclusions: The IVLBCL of this patient showed molecular similarity to non‐GCB DLBCL. Due to the prognostic and increasingly also therapeutic relevance of molecular subtyping in DLBCL, this method, in addition to immunohistochemistry, should also be considered for the diagnosis of IVLBCL in the future. Abstract : What's already known about this topic? Intravascular large B‐cell lymphoma (IVLBCL) is classified as a LBCL according to immunohistochemical and morphological criteria. Diffuse LBCLs (DLBCLs) are molecularly heterogeneous and classified as either non‐germinal centre B‐cell‐ (non‐GCB‐) or GCB type. These subtypes differ in their pathogenesis and clinical outcome, which has led to the investigation of new therapeutic strategies. What does this study add? This is the first molecular classification of IVLBCL. The tumour cells have similarities to non‐GCB DLBCLs and most probably originate from post‐germinal centre B cells. What is the translational message? Molecular classification of IVLBCL could lead to the implementation of new treatment algorithms and improved clinical outcome of patients with this lymphoma.